REGENERAÇÃO DE ESPÉCIES LENHOSAS EM PLANTIO DE SCHINUS MOLLE L. (AROEIRA – PERIQUITA) E TREMA MICRANTHA (L.) BLUME (GRANDIÚVA) - Trindade, Débora F. V. d.; Coelho, Geraldo C. (Salão do Conhecimento, 2013)
Resumo